Crisis and conversion of industrial port complex: the case of Gdansk (Poland) - Maria Lorek (European Regional Science Association (ERSA), 2015)
The Interference of liberal principles and the reintroduction of a market economy have changed the structure and the organization of the productive system of centrally planned and administered countries (NOVE, 1981; ANDREFF, 2007). The new forms of industrial organization, which are the source of these transformations, give priority to territorial logics. In this context, studies on industrial districts, innovative environments, clusters? found renewed interest. However, the issue of local conversion by economic liberalization is still much unexplored in terms of impact on the organization of local actors and the development of innovation on the local level in the former centrally planned countries. The purpose of this paper is to highlight the strong links between the institutional and organizational decentralization and development of innovation on the local level. Our method of analysis is based on the idea that the change of public management after liberalization contributes to the convergence of public and private interests resulting in the emergence of an institutional agent composed of a network of actors. Collective action of these actors plays a vital role in the emergence and development of a potential innovation. To justify our approach, we combine the institutional approach and the evolutionary approach to explain the formation of the institutional agent and its involvement in the development of innovation on the local level. We apply this interpretative framework to the case of industrial port complex of Gdansk because of its economic history, the establishment of the new local economic policy (after 1989), the choice of local authorities, although significant growth of the high-tech sector and the absence of previous study on this issue. The study of institutional change in Gdansk is based on the literature review. The potential of innovation that is forged in parallel is studied on a double level first through a statistical analysis of Gdansk economy to provide an overview on all the initial conditions, then, through the study of data from surveys conducted by the National Statistical Office (GUS) to determine the weight of high-tech enterprises in Gdansk. The results show that the liberalization of exchange considerably affects the organization of local actors in Gdansk. The collective actions of public and private actors are not yet common but they encourage the development of innovation in Gdansk promoting: first, the accumulation of core assets, then the improvement of its scientific and technical potential and third the emergence of innovative high-tech companies. This study shows that the economy of Gdansk is being transformed all by emphasizing the articulation between the different actors of proximity, the local specific resources, and the reports developed on the market and non-market and the introduction of innovation.
Keywords: R11; P21; P25; 330; institutional agent; transition; conversion; innovation; Gdansk